# CS6015: Linear Algebra and Random Processes

## Lecture 36:  Uniform distribution, Normal distribution

\frac{1}{b - a}
b
p_X(x)
f_X(x)

### Continuous Uniform Distribution

a_1
b_1
[
]
P(a_1 \leq X \leq b_1) = \frac{1}{b-a} (b_1 - a_1)
a
b
\dots
\dots
\frac{1}{b - a + 1}
a
b

### Expectation

f_X(x)
p_X(x)
a
b
\dots
\dots
\frac{1}{b - a + 1}
E[X] = \sum_x xp_X(x)
E[g(X)] = \sum_x g(x) p_X(x)
Var(X) = E[X^2] - (E[X])^2
E[X] = \int_{-\infty}^{\infty} xf_X(x) dx
E[g(X)] = \int_{-\infty}^{\infty}g(x) p_X(x)dx
Var(X) = E[X^2] - (E[X])^2

### Mean and variance (Uniform Distribution)

E[X] = \int_{a}^{b} x\frac{1}{b-a} dx
E[g(X)] = \int_{-\infty}^{\infty}g(x) p_X(x) dx
Var(X) = E[X^2] - (E[X])^2
\frac{1}{b - a}
b
f_X(x)
a
b
=\frac{a+b}{2}
E[X] = \int_{-\infty}^{\infty} xf_X(x) dx
E[X^2] = \int_{a}^{b} x^2\frac{1}{b-a} dx
=\frac{1}{b-a}(\frac{b^3}{3} - \frac{a^3}{3})
Var(X) = E[X^2] - (E[X])^2 = \frac{(b-a)^2}{12}
E[X] = \int_{a}^{b} x\frac{1}{b-a} dx
E[X^2] = \int_{a}^{b} x^2\frac{1}{b-a} dx
E[X] =\frac{1}{b-a} * \frac{x^2}{2} |_{a}^b
= \frac{1}{b-a} * (\frac{b^2}{2} - \frac{a^2}{2}) = \frac{1}{b-a}\frac{b^2 - a^2}{2}
= \frac{1}{b-a}\frac{(b - a)(b+a)}{2} = \frac{a+b}{2}
=\frac{1}{b-a} * \frac{x^3}{3} |_{a}^b
= \frac{1}{b-a} * (\frac{b^3}{3} - \frac{a^3}{3}) = \frac{1}{b-a}\frac{b^3 - a^3}{3}
= \frac{1}{b-a}\frac{(b - a)(a^2 + ab + b^2)}{3} = \frac{a^2 + ab + b^2}{3}
Var(X) = E[X^2] - E[X]^2
= \frac{a^2 + ab + b^2}{3} - (\frac{a+b}{2})^2
= \frac{a^2 + ab + b^2}{3} - \frac{a^2 + 2ab + b^2}{4}
= \frac{(b-a)^2}{12}

x^2
e^x
x
e^{-x}
e^{x^2}
e^{-x^2}
20 * e^{-x^2}

e^{-x^2}

### Normal distribution

\mathcal{N}(0, 1) = \frac{1}{\sqrt{2 \pi}}e^{-x^2}
\int_{-\infty}^{\infty} \frac{1}{\sqrt{2 \pi}}e^{-x^2} dx = 1

### Normal distribution

\mathcal{N}(0, 1) = \frac{1}{\sqrt{2 \pi}}e^{-x^2}
E[X] = \int_{-\infty}^{\infty}x\cdot\frac{1}{\sqrt{2 \pi}}e^{-x^2} dx
= 0
Var[X] = E[X^2] - (E[X])^2
= 1

### zero mean, unit variance

\mu = 0, \sigma = 1

### Normal distribution (changing

\mathcal{N}(\mu, 1) = \frac{1}{\sqrt{2 \pi}}e^{-\frac{(x-\mu)^2}{2}}
E[X] = \int_{-\infty}^{\infty}x\cdot\frac{1}{\sqrt{2 \pi}}e^{-\frac{(x-\mu)^2}{2}} dx
= \mu
Var[X] = E[X^2] - (E[X])^2
= 1
\mu = 2
\mu = 0
\mu = -2
\mu)

### Normal distribution (changing

\mathcal{N}(0, \sigma^2) = \frac{1}{\sqrt{2 \pi}}e^{\frac{-x^2}{2\sigma^2}}
E[X] = \int_{-\infty}^{\infty}x\cdot\frac{1}{\sqrt{2 \pi}}e^{\frac{-x^2}{2\sigma^2}} dx
= 0
Var[X] = E[X^2] - (E[X])^2
= \sigma^2
\sigma = 0.5
\sigma = 1
\sigma = 2
\sigma)

### Normal distribution (changing

\mathcal{N}(\mu, \sigma^2) = \frac{1}{\sqrt{2 \pi}}e^{\frac{-(x-\mu)^2}{2\sigma^2}}
E[X] = \int_{-\infty}^{\infty}x\cdot\frac{1}{\sqrt{2 \pi}}e^{\frac{-(x-\mu)^2}{2\sigma^2}} dx
= \mu
Var[X] = E[X^2] - (E[X])^2
\mu = 2, \sigma = 0.5
\mu, \sigma)
= \sigma^2

\mu, \sigma^2

### Normal distribution

\sigma
\sigma
\sigma
\sigma
\sigma
\sigma
\sigma
\sigma
68\%
95\%
99\%
P(\mu - \sigma \leq X \leq \mu + \sigma)
= \int_{\mu - \sigma}^{\mu + \sigma} \frac{1}{\sqrt{2\pi}} e^{ \frac{-(x - \mu)}{2 \sigma^2} } dx
\approx 0.68
P(\mu - 2\sigma \leq X \leq \mu + 2\sigma)
= \int_{\mu - 2\sigma}^{\mu + 2\sigma} \frac{1}{\sqrt{2\pi}} e^{ \frac{-(x - \mu)}{2 \sigma^2} } dx
\approx 0.95